EFFICIENCY OF USE AGRICULTURAL LAND ON THE BASIS FORMATION OF THE EROSION MODEL REGIONAL LEVEL - Y. Butenko; R.Kharitonenko; I.Fesan (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2015)
A general characteristic degradation processes at regional level. The dependence between the coefficients of the properties of agricultural land and soil conservation index value. Calculated losses of major crops due to the use of arable land, which belong to the degraded and unproductive. The measures to restore the effectiveness ofthe use ofthese lands.